Perlindungan Hukum dan Hak Waris Istri Kedua dalam Perkawian Poligami Tanpa Izin - Misda Deni; Asmuni Asmuni; Tengku Erwinsyahbana (Mahesa Research Center, 2020)
Polygamy marriage must be done with the consent or permission of the wife so that this creates a new legal problem regarding the position of the second wife, both in terms of rights and obligations, children, assets in the marriage as well as problems in the distribution of inheritance. The purpose of this paper is to determine the legal protection of a second wife to their legal status in polygamy marriage and to find out the rights of wife's inheritance in polygamy marriage according to Islamic fiqh and positive law. This research method is normative juridical with descriptive analysis research type. Legal protection for the second wife to get the rights and recognition must legalize marriage (isbat nikah) in the Religious Court. The second inheritance right of the wife to the polygamy marriage without permission is the right to inheritance with her husband since the marriage took place and all wives have the same rights to the inheritance within 1/8 if they have children and ¼ if they do not have children.